Kuasa, harapan dan tanah = Power, hope and land - Mohd Yusof Ahmad; Balai Seni Visual Negara (Kuala Lumpur : Balai Seni Visual Negara, 2012)
Selected of artwork presented during exhibition'Power, Hope and Land' in National Visual Art Gallery in conjunction with the celebration of the 55th anniversary of Malaysia's Merdeka Day.
'Untukmu Malaysia...'
English and Malay.
Keywords: Painting, Malaysian -- Exhibitions; Painting, Modern -- 20th century -- Malaysia -- Exhibitions